Specialty of Concept "Creativity " in Architecture - yaser, Maysoon Safi (Iraqi Journal of Architecture and Planning, 2009)
Architecture is one of the most effective changing methods in society. It’s a cultural phenomena that reveal thoughts and believes of its society through its production. That production must have the power to introduce the unique, and which never been known. To achieve that is what could be named "Creativity". The object of this research is concemed with clarif,ing the concept ,,Creativity,, in general, and its specialty in Architecture. The method which have been followed was by: l. Clarifying the concept in philosophy and linguistics theories because of its influence on Architecture. 2. Clarifuing the concept in different theoretical attitudes and strategies that have been used in Architecture. The research concluded that Creativity could be meaning both Revealing and creation. The Revealing would be reached by passed over what have been kaown, and the Creation would be by displacement what has been known.